Association of Temporomandibular Disorder Symptoms with Anxiety and Depression in Saudi Dental Students - Alahmary, Ahmed Wallan (Open Access Maced J Med Sci, 2019)
BACKGROUND: Temporomandibular dysfunction (TMD) is a term that encompasses a set of chronic painful conditions, and dysfunction in the orofacial region involving the muscles of mastication, the temporomandibular joints (TMJ) and related structures. It can affect individuals of any age. AIM: We investigated the prevalence of temporomandibular disorder (TMD) and its association with anxiety and depression. METHODS: Cross sectional study that conducted among 105 dental students (age 20-35 years). The assessment instruments were the Fonseca Anamnestic Questionnaire and the Hospital Anxiety and Depression Scale. RESULTS: TMD was present in 52 (49.5%) students, and anxiety or depression was present in 53 (50.5%) students. The results of the HAD scale showed that 92 (83.4%) students had some level of anxiety or depression, 38 (36.2%) were border line for anxiety or depression, and 80 (76.2%) were diagnosed with anxiety or depression while regarding to the association of TMD with gender, 9 of 48 (17.3%) were males and 39 (82.7%) were females (P-value = 0.001). CONCLUSION: Our study revealed a high prevalence of TMD. The women had a higher prevalence of TMD. Also, we reported the higher prevalence of anxiety and depression among TMD students.